REVIEW ON BIOCHEMICAL ALTERATIONS IN EURYHALINE FISH IN RESPONSE TO CHANGING SALINITIES - SURENDRAN, SURYA; AMPILI, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Euryhaline organisms are exposed to various kinds of stress during their migration to different salinities. To overcome the stress, they are equipped with different osmoregulatory mechanisms including osmotic pressure changes and morphological alterations. Gills, kidneys and intestine are often subjected to biochemical alterations including changes in the concentration of various enzymes working as ion transporters and the endocrine organs support the osmotic balance through hormonal control. This review gives a brief account on these biochemical changes studied in different species to provide an overall idea about the mechanism used by organism to cope with changing salinity.